A Redox-Sensitive Cysteine Is Required for PIN1At Function - Selles, Benjamin; Dhalleine, Tiphaine; Boutilliat, Alexis; Rouhier, Nicolas; Couturier, Jérémy (Frontiers in Plant Science, 2021)
Parvulins are ubiquitous peptidyl-prolyl isomerases (PPIases) required for protein folding and regulation. Among parvulin members, Arabidopsis PIN1At, human PIN1 and yeast ESS1 share a conserved cysteine residue but differ by the presence of an N-terminal WW domain, absent in PIN1At. In this study, we have explored whether the cysteine residue of Arabidopsis PIN1At is involved in catalysis and subject to oxidative modifications. From the functional complementation of yeast ess1 mutant, we concluded that the cysteine at position 69 is mandatory for PIN1At function in vivo, unless being replaced by an Asp which is found in a few parvulin members. This result correlates with a decrease of the in vitro PPIase activity of non-functional PIN1At cysteinic variants. A decrease of PIN1At activity was observed upon H2O2 treatment. The in vitro oxidation of cysteine 69, which has an acidic pKa value of 4.9, leads to the formation of covalent dimers, that are reduced by thioredoxins, or to sulfinic or sulfonic acid forms at higher H2O2 excess. These investigations highlight the importance of the sole cysteine residue of PIN1At for activity. The reversible formation of an intermolecular disulfide bond might constitute a protective or regulatory mechanism under oxidizing conditions.